2011
DOI: 10.1051/0004-6361/201015497
|View full text |Cite
|
Sign up to set email alerts
|

The Ara OB1a association

Abstract: Context. The Ara OB1a association is a nearby complex in the fourth Galactic quadrant where a number of young/embedded star clusters are projected close to more evolved, intermediate age clusters. It is also rich in interstellar matter, and contains evidence of the interplay between massive stars and their surrounding medium, such as the rim HII region NGC 6188. Aims. We provide robust estimates of the fundamental parameters (age and distance) of the two most prominent stellar clusters, NGC 6167 and NGC 6193, … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 37 publications
(41 reference statements)
1
21
0
Order By: Relevance
“…However, they warn that their age estimates might be significantly affected by the uncertainties in the birthline for G‐type stars (see ). More recently, Baume et al (2011) also found a handful of stars with Hα emission typical of accretors in the 20–30 Myr old cluster NGC 6167.…”
Section: Evolution and Metallicity Dependencymentioning
confidence: 89%
“…However, they warn that their age estimates might be significantly affected by the uncertainties in the birthline for G‐type stars (see ). More recently, Baume et al (2011) also found a handful of stars with Hα emission typical of accretors in the 20–30 Myr old cluster NGC 6167.…”
Section: Evolution and Metallicity Dependencymentioning
confidence: 89%
“…Baume et al (2011), (2) Mel'nik & Dambis (2017), (3) Molina-Lera et al (2016), (4) Shull & Danforth (2019), (5) Chené et al (2019), (6) de la Fuente et al (2016), (7) Kurtev et al (2007), (8) Franciosini et al (2018) Gaia DR2 parallaxes. We also note the bulk of objects in our sample are between 2 and 4 kpc.…”
mentioning
confidence: 99%
“…The data are of very high quality, and represent a vast improvement over existing near-IR photometry. Therefore they are useful for a wide variety of studies such as open/embedded clusters (Borissova et al 2011;Baume et al 2011), globular clusters Moni Bidin et al 2011), distance scale (Majaess et al 2011), YSO censuses (Faimali et al, in prep. ), brown dwarfs (Folkes et al, in prep.…”
Section: Discussionmentioning
confidence: 99%